High Frequency Migraine Is Associated with Lower Acute Pain Sensitivity and Abnormal Insula Activity Related to Migraine Pain Intensity, Attack Frequency, and Pain Catastrophizing - Mathur, Vani A.; Moayedi, Massieh; Keaser, Michael L.; Khan, Shariq A.; Hubbard, Catherine S.; Goyal, Madhav; Seminowicz, David A. (Frontiers in Human Neuroscience, 2016)
Migraine is a pain disorder associated with abnormal brain structure and function, yet the effect of migraine on acute pain processing remains unclear. It also remains unclear whether altered pain-related brain responses and related structural changes are associated with clinical migraine characteristics. Using fMRI and three levels of thermal stimuli (non-painful, mildly painful, and moderately painful), we compared whole-brain activity between 14 migraine patients and 14 matched controls. Although, there were no significant differences in pain thresholds and pre-scan pain ratings to mildly painful thermal stimuli, patients had aberrant suprathreshold nociceptive processing. Compared to controls, patients had reduced activity in pain modulatory regions including left dorsolateral prefrontal, posterior parietal, and middle temporal cortices and, at a lower-threshold, greater activation in the right mid-insula to moderate pain versus mild pain. We also found that pain-related activity in the insula was associated with clinical variables in patients, including associations between: bilateral anterior insula and pain catastrophizing (PCS); bilateral anterior insula and contralateral posterior insula and migraine pain intensity; and bilateral posterior insula and migraine frequency at a lower-threshold. PCS and migraine pain intensity were also negatively associated with activity in midline regions including posterior cingulate and medial prefrontal cortices. Diffusion tensor imaging revealed a negative correlation between fractional anisotropy (a measure of white matter integrity; FA) and migraine duration in the right mid-insula and a positive correlation between left mid-insula FA and PCS. In sum, while patients showed lower sensitivity to acute noxious stimuli, the neuroimaging findings suggest enhanced nociceptive processing and significantly disrupted modulatory networks, particularly involving the insula cortex, associated with indices of disease severity in migraine.